Cây chỉ thị nhị phân biểu diễn không gian trạng thái chẩn đoán vi rút tin học - Thủy, Nguyễn Thanh; Quang, Trương Minh Nhật (Journal of Computer Science and Cybernetics, 2016)
Applying problem solving methods and knowledge processing techniques in Artificial Intelligence, we have designed a searching space which helps the inference motor to identify new virus in the form of binary instruction tree. This database structure specifies execution processing of the central processing unit 80x86. It's made to be suitable with installing the searching algorithm. A knowledge based algorithm is combined with some heuristic to speed up the process of searching virus in the tree and increase the confidence of the inference motor.